CURRENT PROBLEMS OF NEXT PRESCHOOL AND PRIMARY EDUCATION - Ye.S. Dehtyar (Academy of Cognitive and Natural Sciences, 2010)
Actual didactic issues nowadays problems of the continuation of preschool and junior education are considered. Scientific aspects , approaches to attain the continuation of pre-school and first-year pupils. The psychological and pedagogical aspects are viewed in the article. Necessity to take into account psychological peculiarities of this age children.